Educação ambiental no Cerrado : ações educativas e conservação da natureza no município de Niquelândia, Norte Goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Environmental Education is an audacious proposal for transforming the pedagogical practice of schools. Environmental Education contributes to the improvement of the individual's relationships, from the moment it addresses his interaction with society and Nature and leads him to reflect and act, giving rise to a critical view of the environmental reality. Environmental Education does not aim to exclude from the curriculum those knowledge that are currently being treated in schools. The contribution of Environmental Education lies precisely in integrating this knowledge and relating it to the problems faced by students and, above all, making them agents capable of acting on this knowledge, in order to build a fairer and more sustainable world. In this way, the pedagogical intervention contributes in a relevant way to the reflection and discussion of themes related to the Environment. In this regard, the general objective of the study was to analyze the actions of Environmental Education developed by schools in the municipality of Niquelândia-GO, in the North Goiano Planning Region, for the conservation and improvements of the urban area. This is a qualitative, descriptive and exploratory research, to be carried out through participant observation, with the use of questionnaires, semi-structured interviews and Field Diary, with qualitative analysis of the data collected through questionnaires and content analysis of the interviews and the researcher's Field Diary. Four schools participated in the study, one of state management and three of municipal management, their respective managers and two teachers for each, totaling eight teachers. The state school developed seven actions within the scope of Environmental Education, while the municipal schools developed between one and two actions, which were recorded by the researcher, as a participant observer, including the registration in photos. The Environment in Schools Program, from the Municipal Environment Department, participated in these actions, through lectures and resources such as fertilizer, vegetable seedlings and native species from the Cerrado and identified drums for selective garbage collection. It was observed that schools were not interested in activating theEnvironment in Schools Program, with the exception of the state school, waiting to be contacted, which is not part of the program's philosophy. After observing and registering the practical activities, reading and analyzing the interviews, it was concluded that the Environmental Education practiced in the four schools is still in the pragmatic phase, that is, it seeks to make the school community aware of the importance of preserving the environment, but still with little reflection and criticism of the causes that led to the degradation which, in the case of the city of Niquelândia-GO, was mining, an activity that is still important for the city's economy. The part of training in Environmental Education also deserves consideration, as many managers and teachers have not done or do not intend to improve in the area, which hinders the development of projects, whether in the present or in the future.
Environmental education in the Cerrado : educational actions and nature conservation in the municipality of Niquelândia, North Goiás
Keywords: Educação Ambiental; Escola Pública; Ensino Fundamental - Niquelândia-GO; Environmental education; Public school; Elementary School - Niquelândia-GO; CIENCIAS HUMANAS::EDUCACAO